Report on Existing Mass Transportation System Bombay - Committee on Plan Projects Planning Commission (Planning Commission, Government of India, 1968)
The 1968 Bombay Metropolitan Transport Report evaluates the city’s mass transportation system, focusing on suburban railways and BEST bus services, in light of rapid population growth and urban expansion. The report identifies severe capacity strains, with suburban trains carrying over 2 million passengers daily and buses frequently operating at full capacity, resulting in overcrowding and safety hazards. Key recommendations include extending railway platforms, enhancing station facilities, installing foot overbridges, and replacing level crossings to improve commuter safety. The report advocates establishing a dedicated traffic study cell, conducting long-term transport planning, and investing substantially in both rail and bus infrastructure. It emphasizes coordination among governmental bodies, urban planners, and transport authorities to ensure an efficient, safe, and sustainable urban transport network capable of meeting future demands.
Metropolitan Transport Team Committee on Plan Projects Planning Commission August 1968
Metropolitan Transport Team Committee on Plan Projects Planning Commission August 1968
Keywords: Bombay; Mass Transportation; Suburban Railways; BEST Buses; Urbanization; Passenger Congestion; Infrastructure Upgrades; Rapid Transit; Traffic Planning; Public Investment; Safety Measures; Long-Term Planning